The Family in Minimum Income Benefits in Europe: An Institutional Analysis. (7th March 2019) - Frericks, Patricia; Och, Ralf; Höppner, Julia
Abstract: Whether and to what extent the means of family members and familial care activities are relevant in the calculation of welfare benefits is often neglected in welfare state analysis. By quantifying qualitative institutional data, we analyze this aspect and how it has changed in regard to minimum-income benefits for persons of pension age and unemployed persons in ten European welfare states. We find no general trend toward individualization of entitlements but a decreasing relevance of family for the entitlements of persons of pension age, and increasing relevance for the unemployed. The evidence underlines significant differences between countries and family-related dimensions.